1Malaysia contemporary art tourism festival Art Boot Camp Perlis (Kementerian Pelancongan dan Kebudayaan Malaysia, 2013)
The camp is a powerful tool to express the participating artist's thoughts, opinions, feelings and perception of environment, experiences and daiy life.This event would assist to position and elevate Malaysia as an international and regional destination for arts in the international tourism arena